Case reportAcne inversa goes an extra mile than hidradenitis suppurativa - Witmanowski, Henryk; Szychta, Paweł; Stępniewski, Sławomir; Mackiewicz-Wysocka, Małgorzata; Czyżewska-Majchrzak, Łucja; Wasilewska, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Acne inversa (AI, hidradenitis suppurativa, Velpeau’s disease, Verneuil’s disease) is a severe, chronic inflammatory dermatosis of unknown etiology, detected on the basis of clinical symptoms more frequently in women than in men. Purulent lesions in the form of nodules and inflammatory tumors, fistulas and scars are present in the areas with hair follicles and apocrine glands, most commonly on the armpits, groin, around the anus and pubic region. Acne inversa can lead to physical and mental disorders. Unfortunately, it is often misdiagnosed and ineffectively treated. The paper presents a case of a 46-year-old patient who was successfully treated surgically for AI around the anus and buttocks by excision of the changes and closure of the wound with local flaps and split-thickness skin grafts, taken with dermatome from the rear surface of the thighs. Surgical treatment is the method of choice in the treatment of severe AI.